Evaluating implementation strategies to support documentation of veterans' care preferences. (8th March 2022) - Carpenter, Joan G.; Scott, Winifred Josephine; Kononowech, Jennifer; Foglia, Mary Beth; Haverhals, Leah M.; Hogikyan, Robert; Kolanowski, Ann; Landis‐Lewis, Zach; Levy, Cari; Miller, Susan C.; Periyakoil, V. J.; Phibbs, Ciaran S.; et al.
Abstract: Objective: To evaluate the effectiveness of feedback reports and feedback reports + external facilitation on completion of life‐sustaining treatment (LST) note the template and durable medical orders. This quality improvement program supported the national roll‐out of the Veterans Health Administration (VA) LST Decisions Initiative (LSTDI), which aims to ensure that seriously‐ill veterans have care goals and LST decisions elicited and documented. Data Sources: Primary data from national databases for VA nursing homes (called Community Living Centers [CLCs]) from 2018 to 2020. Study Design: In one project, we distributed monthly feedback reports summarizing LST template completion rates to 12 sites as the sole implementation strategy. In the second involving five sites, we distributed similar feedback reports and provided robust external facilitation, which included coaching, education, and learning collaboratives. For each project, principal component analyses matched intervention to comparison sites, and interrupted time series/segmented regression analyses evaluated the differences in LSTDI template completion rates between intervention and comparison sites. Data Collection Methods: Data were extracted from national databases in addition to interviews and surveys in a mixed‐methods process evaluation. Principal Findings: LSTDI template completion rose from 0% to about 80% throughout the study period in both projects' intervention and comparison CLCs. There were small but statistically significant differences for feedback reports alone (comparison sites performed better, coefficient estimate 3.48, standard error 0.99 for the difference between groups in change in trend) and feedback reports + external facilitation (intervention sites performed better, coefficient estimate −2.38, standard error 0.72). Conclusions: Feedback reports + external facilitation was associated with a small but statistically significant improvement in outcomes compared with comparison sites. The large increases in completion rates are likely due to the well‐planned national roll‐out of the LSTDI. This finding suggests that when dissemination and support for widespread implementation are present and system‐mandated, significant enhancements in the adoption of evidence‐based practices may require more intensive support.